2022
DOI: 10.2196/37379
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Health Effects of Adding Bicycle and Pedestrian Paths at the Census Tract Level: Multiple Model Comparison

Abstract: Background Adding additional bicycle and pedestrian paths to an area can lead to improved health outcomes for residents over time. However, quantitatively determining which areas benefit more from bicycle and pedestrian paths, how many miles of bicycle and pedestrian paths are needed, and the health outcomes that may be most improved remain open questions. Objective Our work provides and evaluates a methodology that offers actionable insight for city-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…The primary objective is to identify the underlying factors that can categorize variables with similar attributes, thereby reducing the complexity of the variables. Additionally, factor analysis allows for the testing of hypotheses pertaining to the relationships between variables [67,68].…”
Section: Factor Analysismentioning
confidence: 99%
“…The primary objective is to identify the underlying factors that can categorize variables with similar attributes, thereby reducing the complexity of the variables. Additionally, factor analysis allows for the testing of hypotheses pertaining to the relationships between variables [67,68].…”
Section: Factor Analysismentioning
confidence: 99%
“…Understanding health benefits of biodiversity is paramount as research has shown that temperature decreases caused by tree canopies can statistically significantly decrease the number of deaths and doctor visits in an urban area, especially for those age 65 or greater [12,34]. Additional health and lifestyle improvements including high levels of physical exercise, mental well-being, and perceived safety have been linked at a fine-grained geographic level to extent of tree canopy coverage [35,36,37,38]. Furthermore, Li et al found that hospitals in redlined zones have more heat-related outpatient visits and high inpatient admission rates [39].…”
Section: Health Benefits Of Biodiversitymentioning
confidence: 99%
“…It utilizes the principle of ensemble learning, combining multiple decision trees to construct a more robust learning model, thus reducing the problem of overfitting and improving prediction accuracy as a machine learning method. Breiman defined RF as a set of tree-like structures forming a classifier, as shown in (9):…”
Section: Rfmentioning
confidence: 99%
“…In the realm of water resource management, Koop et al [8] applied the geometric aggregation method to enhance the lowest-scoring indicators in integrated water resources management. In studies pertaining to public health, Gore, Ross, et al [9] and Zamponi, Virginia et al [10] employed statistical modeling techniques to assess various aspects of public health. Typically, rating agencies determine the ESG or sustainability scores based on the information disclosed by the companies themselves [11].…”
Section: Introductionmentioning
confidence: 99%